2013
DOI: 10.1093/glycob/cwt109
|View full text |Cite
|
Sign up to set email alerts
|

Glycoxidative damage to human DNA: Neo-antigenic epitopes on DNA molecule could be a possible reason for autoimmune response in type 1 diabetes

Abstract: Advanced glycation end-products (AGEs) are known to be mutagenic, diabetogenic and vascular disease risk factors. Methylglyoxal (MG) is a dicarbonyl species that reacts with biological macromolecule (proteins, DNA and lipids) to give AGEs. Nonenzymatic glycation of MG with lysine (Lys) in the presence of copper (Cu(2+)) is reported to generate reactive oxygen species (ROS) capable of causing DNA damage. We show that DNA modification in MG-Lys-Cu(2+) system results in the generation of strand breaks, base modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Recently, the presence of auto-antibodies in experimental and diabetes mellitus patients against the glycated DNA was investigated by our group [33]–[36]. There are also couple of recent reports for the presence of the auto-antibodies in the sera of the cancer patients which needs to be validated further [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the presence of auto-antibodies in experimental and diabetes mellitus patients against the glycated DNA was investigated by our group [33]–[36]. There are also couple of recent reports for the presence of the auto-antibodies in the sera of the cancer patients which needs to be validated further [37].…”
Section: Discussionmentioning
confidence: 99%
“…A fluorescence study was carried out to confirm the generation of fluorogenic AGEs. Previous studies have revealed that a number of flurogenic AGEs including pentosidine are formed during the glycation process . When native and glycated‐H2A samples were excited at 335 nm, a 96.20% increase in emission intensity at λ max 398 nm was observed relative to the native H2A (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…A 93.74% increase in absorbance (hyperchromicity) at 276 nm as well as increased absorbance between 300 to 400 nm was observed for 3-DG-glycated H1. Assessment of flourogenic pentosidine and formation of different AGEs in 3-DG-glycated H1 histone was investigated by exciting the samples at 335 and 365 nm [ 46 ]. 3-DG-glycated H1 had a 93.37% increase in emission intensity at λ em 395 nm relative to native H1 upon excitation at λ ex 335 nm ( Fig 3A ).…”
Section: Resultsmentioning
confidence: 99%